(3JPcQI GdcMGdjfs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s ((3CMeO Hf fXGe GdOjf GdZQjH s)
(3ChdgG (B:s
(3GdChbGJ Edi GdfXQ ai GdcJH GdcHGQ ai YdGL eQV ef GdCeQGV djSJZfi Hg Yf GdfXQ ai GdcJH GdcHGQ s
(3BNQgG (B:s
(3aEffi GSJYLdJ ai JCdja hLeYg dSQYI MGLJc , aEf cGf Pdc aCUdMg HYO Cf JfYe GdfXQ ajg ,hCf JLYd Ydi ecGaCJi MSf GdOYGA s
(3JfbUs
(3TjFkG jSjQkG ef GdebOeIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs